Composite Contrast Enhancement of Hydrogel-Based Implants for Photon-Counting Computed Tomography Studies - Evgeniya V. Suslova; Denis A. Shashurin; Konstantin I. Maslakov; Stepan Yu. Kupreenko; Tatyana O. Luneva; Oleg S. Medvedev; Georgy A. Chelkov (Gels)
Hydrogels have a wide range of medical applications, including use within implantable systems. However, when used in implants, their visibility under conventional medical imaging techniques is limited, creating safety risks for patients. In the current work, we assessed the possibility of enhancing hydrogels using Ln-based contrasting agents to facilitate their visualization in photon-counting computed tomography (PCCT). The contrast enhancement of gelatin, polyacrylamide (PAM), and silicone shells of implants was assessed. A novel synthetic route for producing cross-linked nanosized Ln2O3 with polyacrylamide was proposed and discussed in detail. Several prototypes of silicone implants, including silicone shell and gelatin or PAM filling with different combinations of contrasting agents, were produced and assessed in phantom PCCT studies.